New estimation of the curvature effect for the X-ray vacuum diffraction induced by an intense laser field. (27th July 2020) - Seino, Y; Inada, T; Yamazaki, T; Namba, T; Asai, S
Abstract: Quantum electrodynamics predicts X-ray diffractions under a high-intensity laser field via virtual charged particles, and this phenomenon is called vacuum diffraction (VD). In this paper, we derive a new formula to describe VD in a head-on collision geometry of an X-ray free-electron laser (XFEL) pulse and a laser pulse. The wavefront curvature of the XFEL pulse is newly considered in this formula. With this formula, we also discuss the curvature effect on VD signals based on realistic parameters at the SACLA XFEL facility.